Electromagnetic physics of the MPA: comprehensive review of applications, design, and analysis of microstrip patch antenas for 5G-technologies - Bernardo, Helton S. [UNESP] (FapUNIFESP (SciELO), 2024)
This work presents a study focused on the electromagnetic evaluation of Microstrip Patch Antennas (MPAs) through electromagnetic simulation for 5G technology applications. The paper addresses two commonly used feeding structures – coaxial probe and transmission line. In our analysis, we observed the scattering and impedance matrices concerning feeding point variations. Additionally, a parametric study explored the impact of relative permittivity, length, width, and height on MPA electromagnetic performance for 5G frequency operation, understanding the physics of these antennas. The results revealed the following: varying the relative permittivity shifted the resonance frequencies and reduced gain; changing the patch length slightly shifted the resonance to lower frequencies without significant changes in the radiation pattern; adjusting the patch width maintained the resonance while increasing matching levels without significant radiation changes; and altering the substrate height shifted the resonance to lower frequencies.
Física eletromagnética da MPA: revisão abrangente das aplicações, projeto e análise de antenas de microfita para tecnologias 5G
Keywords: Communication 5G technologies; Electromagnetic analysis and studies; Physics of the MPAs